1994
DOI: 10.1063/1.355653
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical Kerr effect study of ac susceptibilities in ultrathin cobalt films

Abstract: The ac susceptibility of ultrathin Co/Cu(100) films has been investigated in situ under ultrahigh vacuum conditions using the magneto-optical Kerr effect. A conventional Kerr effect setup was combined with an ac-field modulation technique to improve the experimental detection limit. A sensitivity in the range of 10−8 rad for the Kerr ellipticity has been achieved in the present study. The ac susceptibility χac of the investigated cobalt films is mainly characterized by a pronounced and sharp maximum as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The maximum field which could be applied was 1050 Oe. The dependence of the susceptibility on temperature was measured according to Berger et al 14 to determine the Curie temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum field which could be applied was 1050 Oe. The dependence of the susceptibility on temperature was measured according to Berger et al 14 to determine the Curie temperature.…”
Section: Methodsmentioning
confidence: 99%
“…13,14,15 Hysteresis loops were obtained in static magnetic fields up to B ∼ 30 mT. With the same optical setup the magnetic susceptibility χ(T ) was studied.…”
Section: Experimental Aspectsmentioning
confidence: 99%
“…No additional bias fields were used, hence the zero field ac susceptibility is measured. 13 In this paper we monitor the static susceptibility, which is obtained for sufficiently low magnetic fields and frequencies. The modulation frequency was set to approximately 110 Hz, while the modulation amplitude B mod has been varied on purpose.…”
Section: Experimental Aspectsmentioning
confidence: 99%
“…21 Magneto-optical Kerr effect susceptometry is a versatile tool in modern magnetics materials research. This ac technique, which combines ease of implementation, low cost, and high sensitivity, has been utilized in studies on magnetic phase transitions [22][23][24] and magnetic domain responses 25,26 in thin and ultra-thin magnetic films. Moreover, it has been shown that the imaginary Kerr signal provides additional information on energy absorption in magnetic systems.…”
Section: Introductionmentioning
confidence: 99%